Answer :

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation



And either of their sum or difference = b


Thus the two terms are

Difference =

Product =

√3 x(x + 4√3 )-2(x + 4√3) = 0

(√3 x-2)(x + 4√3) = 0

Hence roots of equation are

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses